2019
DOI: 10.15666/aeer/1706_1351313521
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Weed Management in Dry Lentil Fields

Abstract: A questionnaire consisting of 20 questions about weed, herbicide, tillage and crop rotation was applied to 100 lentil farmers to determine the current state of a weed problem in lentil fields in 2016. Common weeds were determined charlock mustard (Sinapis arvensis L., 36%), devil-on-all-sides (Ranunculus arvensis L., 16%), cleavers (Galium aparine L., 11%), makhobeli (Cephalaria syriaca L., 8%), and knapweed (Centaurea depressa L., 8%), respectively. The majority of participants used aclonifen (89%) as a post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In fact, glyphosate and AMPA significantly inhibited AChE activity in the gills of Mytilus galloprovincialis exposed in vivo to the contaminants for 7 and 21 days [67]. Similar results were obtained in other bivalve species, crustaceans and fish for glyphosate [68][69][70]. Surprisingly, in our study, an increased presence of larval abnormalities was not found in the Roundup 100 µg/L exposure, even if the concentration of the active substance was the same.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, glyphosate and AMPA significantly inhibited AChE activity in the gills of Mytilus galloprovincialis exposed in vivo to the contaminants for 7 and 21 days [67]. Similar results were obtained in other bivalve species, crustaceans and fish for glyphosate [68][69][70]. Surprisingly, in our study, an increased presence of larval abnormalities was not found in the Roundup 100 µg/L exposure, even if the concentration of the active substance was the same.…”
Section: Discussionsupporting
confidence: 88%
“…Farming system was the main source of variation for both losses, while early flowering and small seed size were traits associated with low losses (Vlachostergios et al 2018). Lentil yield loss from the competition with weeds can range as high as 80% (Pala 2019).…”
Section: Reduction In Yield and Quality Due To Biotic Stressesmentioning
confidence: 99%
“…However, these herbicides have harmful effects on the environment and human health (Andreotti et al 2018;Elsakhawy et al 2020). To control Orobanche in lentil, the doses of glyphosate used prove to be phytotoxic and its reduction decreases the effectiveness of treatment (Pala 2019). The use of other solutions preserving the crop and the environment are being sought.…”
Section: Introductionmentioning
confidence: 99%